Las culturas juveniles en las ciudades medias. Un estudio de caso - Feixa i Pampols, Carles (El Colegio de México A.C., 1994)
How cultural identities are constructed in middle-size cities? How young people participate in the articulation of these identities? The emergence of youth as new social subject leads to the creation of a set of specifics spaces and times in the urban scene. This article presents a case study made in a middle-size city in Catalonia and aims to encourage research on youth cultures in Mexico.